Analysis of Legal Aspects Related to Special Narcotics Crimes as Extraordinary Crimes - Putri, Darma; Baginda, Baginda (CV. Rayyan Dwi Bharata, 2024)
The Narcotics crimes are special crimes outside the Criminal Code, this is stated explicitly in Article 25 of Government Regulation Number 24 of 1960 which came into effect on June 9 1960 concerning the investigation, prosecution and examination of criminal acts. Special criminal law is criminal law established for special groups of people, including military criminal law (special groups of people) and fiscal criminal law (special actions) and economic criminal law. The formulation of the problem in this study is how the how to analyze the legal aspects related to special narcotics crimes as extraordinary crimes and what are the negative impacts related to special narcotics crimes on victims as extraordinary crimes. The research method used by the author is normative juridical method carried out through literature studies that examine secondary data in the form of laws and regulations relating to narcotics, and narcotics crime laws as well as research results and other references. This research uses a type of normative legal research because of the provisions regarding the analysis of narcotics crimes as extraordinary crimes. The results of this study are in With the existence of laws, criminal law is born. The formation of statutory sanctions is determined by the legislator which requires the realization of an agency in ways that can actually apply or implement the criminal regulations in question. To realize this crime, infrastructure is needed. Criminal sanctions aim to provide special suffering to violators so that they are deterred by the consequences of their actions. Criminal sanctions are also a form of statement of condemnation of the perpetrator's actions. The principle difference between criminal sanctions and criminal sanctions is also often referred to as the presence or absence of blame, not the presence or absence of the element of suffering. Meanwhile, action sanctions have a more educational purpose. Narcotics crime is a dangerous crime, damaging the younger generation as well as the character and physique of society or its users. These crimes can also be linked to a number of crimes, such as robbery, theft, money laundering and terrorism. Therefore, the consequences of narcotics use not only have a negative impact on the user himself but also directly or indirectly affect the family, community and country. This narcotics crime has been going on since the era of independence until now.